LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PERMAINAN KERJASAMA UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA - Oni Titik Wahyuning Rici; Tuty Alawiyah (IKIP Siliwangi, 2019)
The purpose of this research is to find out whether the application of cooperation game techniques can improve social skills in students. The approach in this research is a quantitative approach with a quasi experimental research method. Based on the test results, it is known that the sig (2-tailed) value is 0.000 <0.05, then H0 is rejected and Ha is accepted. With the results of the calculation of the average score of social skills before being given treatment was 87.1 and after being given treatment, cooperative game techniques in improving social skills in students tended to increase by 126. It can be concluded that there is an average difference between the pretest and posttest results, which means there is an influence in the application of cooperative game techniques to improve social skills in class VIII B students at SMPN 2 Batujajar in Kab. West Bandung.Keywords: Social skills, cooperative games, group guidance